2021
DOI: 10.2147/jmdh.s314191
|View full text |Cite
|
Sign up to set email alerts
|

The Effects on the Number of Patients Visiting the Emergency Units: Comparison Study Before and During COVID-19 Pandemic in Saudi Arabia

Abstract: Background The number of patients attending emergency departments (EDs) fell dramatically in 2020, during the COVID-19 pandemic, compared with similar periods in 2019 or 2018, and healthcare providers have had to adjust to this change. The aim of this study was to compare the number and type of patients attending a hospital emergency unit before and during the COVID-19 pandemic in order to avoid the impact of any difference on the community’s healthcare and on healthcare providers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…Of them, the number of patients with fever decreased by 19.5% (931 during the pre-COVID-19 vs. 749 during the COVID-19 period). This trend was similar to that reported in previous studies [17,18]. The major contributing factor for the decrease in ED visits during the pandemic was probably the fear of patients being exposed to COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Of them, the number of patients with fever decreased by 19.5% (931 during the pre-COVID-19 vs. 749 during the COVID-19 period). This trend was similar to that reported in previous studies [17,18]. The major contributing factor for the decrease in ED visits during the pandemic was probably the fear of patients being exposed to COVID-19.…”
Section: Discussionsupporting
confidence: 90%
“…Studies conducted in KSA to investigate the influence of COVID-19 pandemic on the volume and acuity of patients presenting in ERs revealed an overall reduction in the total number of patients; however, a significant increase in the number of patients attending the ERs as higher acuity was also noticed. 3 , 4 The increment of the number of patients with higher acuity was about 200% resulting in an overcrowding and delay in ERs services. 4 This increase in the number of patients with a higher acuity has interfered with patient flow and put health-care providers and other patients at high risk of infection with the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, patients with high acuity illness or injury may have had to wait far too long to be adequately treated. Previous studies had found that patients with lower acuity were avoiding visiting ED during the COVID-19 pandemic in Saudi Arabia [ 19 , 21 ] and other health systems [ 18 , 19 , 21 , 23 , 24 ]. In our study population, the number of ED visits declined after COVID-19 [ Appendix A ].…”
Section: Discussionmentioning
confidence: 99%
“…All of this increased the workload which led to crowding in the ED [ 13 , 14 , 15 , 16 ]. On the other hand, there was a decreased volume of patients seeking health care [ 17 , 18 ] or visiting ED during the COVID-19 pandemic, especially those presenting as lower acuity [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%